Implementasi Educational Comic Berbasis Aplikasi Comic Life sebagai Media Pembelajaran Alternatif - Damayanti, Fitri; Supriyatin, Titin (Universitas Nusantara PGRI Kediri, 2022)
The era of the industrial revolution 4.0 requires educators to make reforms in the teaching and learning process. Textbook material that only contain writing makes student difficult to understand the content and lead to low student literacy. Learning media is needed as a supporting media so that learning is more effective and cognitive learning outcomes are achieved. This community service activity was partnered with Ar-Ridwan High School, Bekasi in the form of training on educational comics. The training was provided online due to the Covid-19 pandemic. One of the educational comic applications that can be used is Comic Life. This training were expected to increase students' scores, students' interest in learning, and improve student literacy. Partners agree that the training provided could increase students' interest in literacy. In addition, educational comics were also able to create a sense of pleasure and interest in students to learn a learning material. Partners also agree that the application of Comic Life was easier to apply due to not require drawing skills which comic illustrations could be in the form of photo collages and were not constrained by the internet due to this application was non based on web.